Decursin Inhibits Expression and Nuclear Localization of DNMT and HDAC, and Suppresses the Growth and Survival of Prostate Cancer Cells - Dwivedi, Lalita; Jaiswal, Aishwarya; Punia, Reenu; Suresh Kumar, R.; Yim, Dongsool; Rajamani, Paulraj; Singh, Rana P. (Asian Pacific Journal of Cancer Biology, 2024)
Background: DNA methyltransferases (DNMT) and histone deacetylases (HDAC) inhibitors have utility in cancer therapeutics. However, they are associated with toxicity, which limits their efficacy against carcinomas. Previously, we reported that decursin has anticancer activity against prostate cancer (PCa). In this study, we investigated its epigenetic role in inhibiting the survival of PCa cells. Methods and Results: PCa cell viability was evaluated using MTT and trypan blue assays. The effect of decursin on global methylation and gene-specific methylation was assessed by dot blot assay and MS-PCR, respectively. Differential expression of DNMTs and HDACs was analyzed through semi-quantitative RT-PCR and western blotting. The activity of these enzymes was measured using commercial kits. The nuclear localization of DNMTs and HDAC3 was assessed via immunoblotting. Results: Decursin decreased cell viability and global methylation in PCa cells. It diminished the expression of DNMT1, DNMT3A, DNMT3B, and pan-DNMT activities. Decursin also reduced nuclear levels and increased cytosolic levels of DNMT1 and DNMT3A. Additionally, it inhibited the expression and activity of HDACs, leading to increased total acetylation and H3K9/14 acetylation of histone H3. A reduction in nuclear localization of HDAC3 was observed in decursin-treated PCa cells. Overall, decursin reduced DNMT and HDAC expression and enhanced the nuclear export of DNMT1, DNMT3A, and HDAC3, leading to decreased activities of these enzymes. Conclusion: This study demonstrates the potent anticancer effects of decursin in prostate cancer cells through modulation of epigenetic mechanisms. Decursin decreased both overall and nuclear levels of DNMTs and HDACs. This effect is likely due to decursin’s inhibitory action on these enzymes, as indicated by decreased global methylation and increased histone H3 acetylation. These findings suggest that decursin has multi-faceted epigenetic modulatory properties, making it a promising therapeutic agent for prostate cancer prevention.